Personality and basic psychological needs as predictors of life satisfaction - Butković, Ana (Array, 2014)
The goal of this study was to replicate in three samples of different age previous finding that basic psychological needs predict life satisfaction over and beyond personality. First sample consisted of 218 high-school students, second of 206 university students, and third of 182 participants aged between 35 and 45 years. All participants filled in Basic Psychological Needs Scale, Big Five Inventory and Satisfaction with Life Scale. Personality explained 8%, 25% and 21% of life satisfaction variance in three samples, respectively. Psychological needs explained 25%, 40% and 50% of life satisfaction variance in three samples, respectively. So, psychological needs explained more life satisfaction variance than personality, and amount of explained variance was increasing with age. Also, psychological needs explained additional variance over personality (16%, 17% and 29% in three samples, respectively), while personality has not contributed significantly to explaining life satisfaction variance over and beyond psychological needs.